if xy > 0, does (x - 1)(y - 1) = 1 ? (1) x + y = xy (2) x : DS Archive
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 21 Jan 2017, 04:05

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

if xy > 0, does (x - 1)(y - 1) = 1 ? (1) x + y = xy (2) x

Author Message
Manager
Joined: 05 Jul 2006
Posts: 197
Followers: 1

Kudos [?]: 60 [0], given: 0

if xy > 0, does (x - 1)(y - 1) = 1 ? (1) x + y = xy (2) x [#permalink]

Show Tags

25 Oct 2006, 07:33
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

if xy > 0, does (x - 1)(y - 1) = 1 ?
(1) x + y = xy
(2) x = y
Manager
Joined: 31 Aug 2006
Posts: 213
Followers: 1

Kudos [?]: 2 [0], given: 0

Show Tags

25 Oct 2006, 07:40
(A)

xy>0 implies x!=0 and y!=0
and x,y are both +ve or x,y are both -ve

Stat(1) - gives only one value , x=y=2 - Hence Suff
Stat(2) - gives two values x=y=1 and x=y=2 - Hence Insuff
Senior Manager
Joined: 01 Sep 2006
Posts: 301
Location: Phoenix, AZ, USA
Followers: 1

Kudos [?]: 26 [0], given: 0

Show Tags

25 Oct 2006, 07:41
(1) x+y=xy==> x= y(x-1) or y=x(y-1)
(x-1) = x/y and (y-1)=y/x
(x-11)(y-1)= xy/xy==1

Suffcient

(2) x=y==> (x-1)(y-1)=(x-1)(x-1)=(x^2-1)

assume x=1 (x^2 -1 ) = 0
assume x = -2 ( x^2 -1) = 3

Insuff
SVP
Joined: 01 May 2006
Posts: 1797
Followers: 9

Kudos [?]: 149 [0], given: 0

Show Tags

25 Oct 2006, 11:44
(A) also

(x - 1)(y - 1) = 1?
<=> x*y - x - y + 1 = 1 ? (1)

Stat 1
x + y = xy
<=> x*y - x - y = 0
Thus,
x*y - x - y + 1 = 0 + 1 = 1 => (1) is verified.

SUFF.

Stat 2
x=y
=> x*y - x - y + 1 = x^2 - 2*x + 1 : can be equal to 1 if x = 2 or x = 0 but can be equal to any things else

INSUFF.
25 Oct 2006, 11:44
Display posts from previous: Sort by